Incidence trends and associated factors of diabetes mellitus in Korean children and adolescents: a retrospective cohort study in Busan and Gyeongnam - Jung Hyun Lee; Yu-Mi Kim; Min Jung Kwak; Su Yung Kim; Hyun-Ji Kim; Chong Kun Cheon; Woo Yeong Chung; Im-Jeong Choi; Su Young Hong; Hee Won Chueh; Jae-Ho Yoo (Annals of Pediatric Endocrinology & Metabolism, 2015)
PurposeThis study investigated the incidence trends and associated factors of type 1 (T1DM) and type 2 diabetes mellitus (T2DM) in children and adolescents under 15 years of age in Busan and Gyeongnam, Korea from 2001 to 2010.MethodsMedical records of newly diagnosed diabetes patients (n=328; 160 males, 168 females) were collected in questionnaire form from 5 tertiary and 42 general hospitals in Busan and Gyeongnam.ResultsThe average crude incidence rate of T1DM and T2DM was 2.01/100,000 (95% confidence interval [CI], 1.76-2.28) and 0.75/100,000 (95% CI, 0.60-0.92), respectively. The incidence rate ratio (IRR) of T1DM was 1.31 (95% CI, 1.01-1.69), and that of T2DM was 1.97 (95% CI, 1.25-3.11) in the latter half-decade (2006 to 2010) compared to the early half-decade (2001 to 2005). There were gradually increasing incidence trends in both T1DM and T2DM over the 10-year period (P for trend: T1DM, 0.0009; T2DM, <0.0001). Age-specific IRR was highest in the 10- to 14-year-old group, regardless of diabetes type. In particular, a rapid increase in incidence of T2DM occurred in the 10- to 14-year-old group. IRR for females was 1.07 (95% CI, 0.83-1.38) for T1DM and 1.56 (95% CI, 1.01-2.41) for T2DM. IRR for Busan (urban) was 1.41 (95% CI, 1.09-1.83) for T1DM and 1.49 (95% CI, 0.96-2.30) for T2DM.ConclusionT1DM and T2DM incidence both increased over time in youth under age 15 living in Busan and Gyeongnam; in particular, the incidence of T2DM in adolescents increased more rapidly.